Difference of Vertical Transmission in HIV-Infected Women with Complete and Incomplete PMTCT - Fausihar, Sitti; Saroyo, Yudianto B (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To analyze any differences on vertical transmission in groups with complete and incomplete program as well as the factors influencing completion. Method: This was a retrospective cohort study performed by data collection from medical records and/or interviews from January 2010 to February 2012. The variables analyzed subject characteristics, applied PMTCT program and risk factors affecting transmission. Result: Seventy-five pregnant women who were HIV-positive were initially recruited, but 21 subjects were excluded due to incomplete medical records. In the first group (n=27) who received complete PMTCT, no vertical transmission was identified, while in the second group (n=27) with incomplete PMTCT, seven children were found to be HIV-positive. Rupture of membrane for more than 4 hours was the only significant risk factor for vertical transmission (p=0.001, RR=64.5, 95% CI=6.14-677.6). Conclusion: There was a significant difference in the occurrence of vertical transmission between complete and incomplete PMTCT program. Complete PMTCT program may provide protective effect against the occurrence of vertical transmission by 25.9%. Keywords: HIV, PMTCT, vertical transmission